Modelling the demand for inbound medical tourism : The case of Malaysia - Tang, Chor Foon; Lau, Evan Poh Hock (John Wiley and Sons Ltd, 2017)
This paper empirically examines the macroeconomic determinants for medical tourism demand using time series econometrics methodology. We find that income, price, exchange rate, SARS outbreak, safety, medical quality, manpower, and medical facilities are significantly affecting the long-run demand behaviour of medical tourism in Malaysia. In order to attract medical tourists, policymakers in Malaysia should (a) reduce the medical prices, (b) reduce the crime rate and improve safety, and (c) continue the improvement of research, medical quality, manpower, and facilities to support the revolution of inbound medical tourism demand in Malaysia. This is to ensure the Malaysia's sustainable economic development